Effect of brine concentration and curing time on quality attributes of cooked turkey laps (2014)
The objective of this study was to investigate the effect of brine concentration and curing time on physicochemical, microbial and sensory characteristics of turkey laps. 4 turkey laps of weight between 1.00 - 1.5kg were divided into 4 treatment groups of brine concentration - 10, 15, 20 and 25% respectively and were cured for 0, 4 and 8 days after cooking at 72°C for 20min. The results showed that Water Holding Capacity (W 1C) and pH of the cured turkey laps increased (p<0.05) as cooking loss decreased p<0.05) thereby increasing the yield of the turkey laps after cooking. Total Viable Count (TVC) and Total Coliform Count (TCC) decreased (p<0,05) while Total Fungal Count (TFC) increased (p<0.05) as brine concentration increased, but the TVC and TCC fluctuated while TFC increased steadily as curing time, increased, not above tolerable levels which made the turkey laps wholesome and safe for consumption. Colour, flavour, texture and juiciness scores increased (p<0.05) as the brine concentration and time of curing increased, but were higher (p<0.05) in turkey laps in treatment 3 that were cured for 4 days. It was observed that treatment 3 (20% brine) and curing for 4 days furnished higher quality attributes of turkey laps as pH, WHC and moisture were high considerably thereby increasing the yield while cooking loss decreased. Also the microbial, counts were lower while colour, flavour, texture and juiciness were higher. In the overall assessment of turkey laps, those cured with 20% brine for 4 days were most acceptable to sensory panel members.